Hypoxia Induced by Upconversion‐Based Photodynamic Therapy: Towards Highly Effective Synergistic Bioreductive Therapy in Tumors1. Issue 28 (26th May 2015) - Liu, Yanyan; Liu, Yong; Bu, Wenbo; Cheng, Chao; Zuo, Changjing; Xiao, Qingfeng; Sun, Yong; Ni, Dalong; Zhang, Chen; Liu, Jianan; Shi, Jianlin
Abstract Local hypoxia in tumors is an undesirable consequence of photodynamic therapy (PDT), which will lead to greatly reduced effectiveness of this therapy. Bioreductive pro‐drugs that can be activated at low‐oxygen conditions will be highly cytotoxic under hypoxia in tumors. Based on this principle, double silica‐shelled upconversion nanoparticles (UCNPs) nanostructure capable of co‐delivering photosensitizer (PS) molecules and a bioreductive pro‐drug (tirapazamine, TPZ) were designed (TPZ‐UC/PS), with which a synergetic tumor therapeutic effect has been achieved first by UC‐based (UC‐) PDT under normal oxygen environment, immediately followed by the induced cytotoxicity of activated TPZ when oxygen is depleted by UC‐PDT. Treatment with TPZ‐UC/PS plus NIR laser resulted in a remarkably suppressed tumor growth as compared to UC‐PDT alone, implying that the delivered TPZ has a profound effect on treatment outcomes for the much‐enhanced cytotoxicity of TPZ under PDT‐induced hypoxia.